Theoretical Performance of Silica Gel Desiccant Wheel - Zainab Mahdi Salih; Abdulsalam D. M.Hassan; Amer Majeed Al-Dabagh (Wasit Journal of Engineering Sciences)
Abstract— Silica gel is a substance commonly used in desiccant wheel, which in turn is used in many applications to reduce moisture from the supplied air to a specific space. In this research,  the effect of different operational conditions on the performance of silica gel wheel were studied. The desiccant wheel, which has been used, has a diameter of 55 cm and thickness of 20 cm. It contains 34 kg of silica gel and rotate at a speed of 30 rph. The theoretical performance coefficients of the desiccant wheel which have been studied include ,moisture removal capacity(MRC),dehumidification performance(DCOP),latent coefficient of performance (COPlat), and desiccant wheel effectiveness(ϵ_d). The theoretical investigation of these coefficients was done by using Novel Aire Technology software program (Simulation program of desiccant wheel) (2012). While the operational conditions like process air (humid air)inlet temperature between(30 to 43.4)0C, process air inlet humidity ratio between (0.011 to 0.019)kg/kgdry air ,regeneration air inlet temperature between (56.5 to 70)0C,and process air mass flow rate between(0.0814 to 0.199)kg/s. The results shows that the effectiveness and the moisture removal capacity have the same behavior increase with the increasing in mass flow rate from(0.0814 to 0.199) kg/s, humidity ratio from(11 to19)g/kgdry air, and regeneration air temperature from(56 t0 70)oC. But they reduces with increasing of inlet process air temperature from(30 to43.4)oC..